2021
DOI: 10.1007/s10637-021-01062-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cetuximab as preemptive postsurgical therapy for oral squamous cell carcinoma patients with major risk: a single‐center retrospective cohort study

Abstract: SummaryA retrospective cohort study was performed to investigate the effectiveness of preemptive postsurgical therapy with cetuximab for patients with a major risk of recurrence or metastasis after clinical complete resection of primary oral squamous cell carcinoma (OSCC). The study period was from 2007 to 2019 for patients treated at the Department of Oral and Maxillofacial Surgery, Dokkyo Medical University School of Medicine. OSCC patients with major risk (n = 88) in the follow-up period were divided into g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Since the study was performed over the course of 14 years, treatment strategies varied over time, but general clinical factors were examined for the patients who were at major risk for a poor outcome and in cases where postsurgical treatment was considered. In the early part of the study period, this treatment was mainly platinum-based chemotherapy alone or combined with RT, as described in the NCCN guidelines, but after the introduction of cetuximab, postsurgical treatment including cetuximab became common as a preemptive therapy for dormant cancer cells [ 4 ]. After the completion of postsurgical treatment, the oral administration of S-1 was recommended for all patients as adjuvant therapy at 1 year after surgery [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the study was performed over the course of 14 years, treatment strategies varied over time, but general clinical factors were examined for the patients who were at major risk for a poor outcome and in cases where postsurgical treatment was considered. In the early part of the study period, this treatment was mainly platinum-based chemotherapy alone or combined with RT, as described in the NCCN guidelines, but after the introduction of cetuximab, postsurgical treatment including cetuximab became common as a preemptive therapy for dormant cancer cells [ 4 ]. After the completion of postsurgical treatment, the oral administration of S-1 was recommended for all patients as adjuvant therapy at 1 year after surgery [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The guidelines for head and neck cancer by the National Comprehensive Cancer Network (NCCN) indicate extranodal extension, positive margins, close margins, pT3 or pT4 primary, pN2 or pN3 nodal disease, nodal disease in levels IV or V, and perineural, vascular, and lymphatic invasion as adverse features (AFs) for a poor postsurgical outcome [ 1 ]. We extracted extranodal extension, positive margins, close margins, pN2 or pN3 nodal disease, and nodal disease in levels IV or V among the AFs and defined them with the addition of the Yamamoto–Kohama (YK) mode of invasion [ 2 , 3 ], with YK-4C and YK-4D as the major risk factors for recurrence or metastasis [ 4 ]. We have used these risk factors since 2014, and we have found that patients with these factors have significantly poorer outcomes and that these outcomes are significantly improved using combination therapy with cetuximab and paclitaxel [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many cancers including head and neck cancer have been treated by molecular-targeted drugs in addition to surgery, chemotherapy, and radiotherapy [1,2]. Acute promyelocytic leukemia can be treated by all-trans retinoic acid (ATRA), which is a molecular-targeted drug and has a differentiation-inducing activity [3,4].…”
Section: Introductionmentioning
confidence: 99%